Elucidating the role of the HBV e antigen in manipulating the innate immune response. (April 2015) - Revill, Peter A; Visvanathan, Kumar; Locarnini, Stephen A
ABSTRACT : HBV causes persistent infection in approximately 300 million people and is associated with up to 2 million deaths annually. While the mechanisms by which HBV establishes and maintains infection are yet to be fully elucidated, there is mounting evidence that HBV infection in humans upregulates a range of innate immune responses and HBV has in turn has evolved mechanisms to suppress these responses. One such mechanism may be the hepatitis B e antigen (HBeAg), a soluble secreted protein which is also a major driver of adaptive immune responses. In this review, we review the literature on HBeAg-mediated regulation of innate immune responses and show that this regulation may extend beyond hepatocytes to other cell types such as NK cells which play an important role in viral clearance. Although further studies using new infection models are required, taken together these findings suggest that the HBeAg is an important regulator of the host response to infection and should not be overlooked in efforts to identify novel therapeutic targets against HBV.